El aporte de la inteligencia artificial en los procesos contables y financieros de la Empresa INCAFOE - Godoy Romoleroux, Nicolle Andrea (2024)
This research examines the contribution of artificial intelligence (AI) to INCAFOE's accounting and financial processes, exploring how it can improve the quality and efficiency of financial reporting. The study addresses the rapid transformation that AI is bringing about in accounting, highlighting both the advantages and challenges associated with its implementation, such as improved decision making and process optimization versus security risks and resistance to change. The overall objective of the research is to determine the impact of AI on INCAFOE's accounting processes, assessing its influence and reliability in financial reporting. To achieve this end, a mixed methodological approach was adopted, combining quantitative analysis of financial statements and semi-structured interviews with key personnel. This methodology allowed for a holistic understanding of the effects of AI, encompassing both numerical aspects and staff perceptions of its daily use. The main results reveal that AI has had a significant impact on the operational efficiency and accuracy of financial reporting at INCAFOE. Automation of repetitive tasks has freed up time for professionals to focus on higher value-added activities, improving decision making and reducing the risk of human error. However, distrust and perceived risk associated with data security and investment in new technologies persist as significant barriers.